BBDSM Belajar Mapel SD : Basa Basi dengan Si Manis (Belajar Asik Belajar Santai dengan Simpel, Inovatif, Menyenangkan dan Humanis) di SD N 1 Takmung: Belajar Mapel SD : Basa Basi dengan Si Manis (Belajar Asik Belajar Santai dengan Simpel, Inovatif, Menyenangkan dan Humanis) di SD N 1 Takmung - Muliani, Ni Made; Putra, Ida Bagus Komang Sindu; Indrayani , Anak Agung Diah; Trisnadewi, Komang; Muniksu, I Made Sukma; Widiantana, I Kadek; Pastika, I Gede Tilem; Wijaya, I Komang Wisnu Budi (Sevanam: Jurnal Pengabdian Masyarakat, 2023)
The Covid-19 pandemic has had an impact on the world of education, elementary school students must undergo online learning. Online learning is certainly a new thing for most students, this learning should be an alternative in helping the delivery of material by teachersas well as attracting students to be more enthusiastic in learning at home. The community service team from the Faculty of Dharma Acarya UHN I Gusti Bagus Sugriwa Denpasar wants to help elementary school students to have a fun, fun, innovative and humane learning experience through videos. The hope is that students have a deep understanding of the material, but the learning process is carried out in a fun, relaxed and fun way through interesting learning videos that can be directly practiced by students and there are rewards for students who are active in following each lesson. The material provided can also be used as further learning material by teachers. The method in this community service activity is to provide online learning for the subjects of Mathematics, Balinese, English, Science and Art using media in the form of videos in a fun, relaxed, simple, fun, innovative and humanist manner. The result of this activity is Basa Basi online learning with Si Manis One which uses media in the form of learning videos for Elementary School Chapel to grade V students of SD N 1 Takmung can provide positive learning results and good impressions are obtained from grade V students of SD N 1 Takmung after obtaining Basa Basi online learning with Si Manis.